The effect of price increases on predicted alcohol purchasing decisions and choice to substitute - Hobday, M.; Gordon, E.; Lensvelt, E.; Meuleners, L.; Liang, W.; Chikritzhs, Tanya (Informa Healthcare, 2016)
Introduction: Few studies have undertaken to explore whether people who consume particular alcoholic beverages have a greater tendency to substitute with cheaper alcohol in response to price increases. The aim of this study was to investigate the effect of price increases on alcohol purchasing decisions, specifically the influence on brand and cross-beverage substitution across demographic, drinking level and socio-economic factors. Method: Data on participants’ alcohol purchasing habits and consumption were collected via an online survey, including their reactions to three price increases to alcoholic beverages types previously purchased. Data were analysed using logistic regression, with substitution behaviour the dependent variable, controlling for demographic and socio-economic factors. Results: Responses to different price increases varied by drinking level, which was consistently and significantly associated with likelihood of substitution behaviour across beverage types. For a 50% increase in price, regardless of whether participants purchased beer, wine, bottled spirits or premixed spirits, drinking at levels which put participants at high risk of short-term harms was associated with a higher likelihood of substitution with cheaper brands or beverage types (OR: 1.729; OR: 1.787; OR: 1.729 and OR: 1.729, respectively). Conclusions: No consistent trends in responses occurred according to respondent characteristics, suggesting that increasing price may be an effective tool to influence purchasing behaviour across the population. Results also suggested that those who drink at levels which put them at high risk of short-term harms may be more likely to circumvent price increases by switching to a cheaper product.